Optimization of Traffic Dikmas Unit by Dikyasa Traffic Unit in Preventing Traffic Violations Against Students in the Jurisdiction of the Bogor Police - Sultan, Mahafidz (Police Studies Review, 2024)
This research is motivated by the highest number of traffic violation which is conducted by students on regional of law of Bogor police station. The minimum of students’ awareness so that Satlantas Bogor Police Station made a program named Dikmas Lantas that did by Unit Dikyasa to students in hopes of increasing awareness and knowledge for the students about how important obey the traffic rules on regional of law of Bogor police station. The formulation of the problem is this research is motivated by the highest number of traffic violation which is conducted by students on regional of law of Bogor police station and the minimum of students’ awareness. The purpose of this writing is to describe and analyze implementation of activities of Dikmas Lantas by Unit Dikyasa in order to avoid traffic violation by the students on regional of law of Bogor police station. To describe and optimize about the obstacles which come during implementation of Dikmas Lantas to the students. To identify and analyze the factors that affect implementation of Dikmas Lantas by Unit Dikyasa to avoid traffic violation by students on regional of law of Bogor police station. This research is using qualitative inquiry.